A Novel Concept of the “Standard Human” in the Assessment of Individual Total Heart Size: Lessons from Non-Contrast-Enhanced Cardiac CT Examinations - Maciej Sosnowski; Zofia Parma; Marcin Syzdół; Grzegorz Brożek; Jan Harpula; Michał Tendera; Wojciech Wojakowski (Diagnostics, 2025)
Background: This single-center retrospective observational study reviewed data from 2305 persons examined for coronary artery calcium (CAC) with non-contrast-enhanced cardiac CT. Other cardiac structures, including chamber volumes, were evaluated besides the CAC scoring. We proposed a novel body size indexing measure that may outperform common indices for quantifying total heart volume (THV). Methods: This index is the sum of height and the difference between height (unitless) and body surface area (unitless), [h+(h-BSA)], and if the (h-BSA) equals “zero”, it is a feature of the “standard human”. Results: We found that, in subjects with a low cardiovascular (CV) risk, the THV normalized for the novel index was simply a function of BW gain, being the highest in obese. If high-CV-risk features (hypertension, diabetes) were present, the measured THV was larger than expected for BW gain, exceeding values observed in low-CV-risk ones. Differences were found to be sex-independent in all BMI categories. Conclusions: Common BSA correction hides these differences and makes the prognostication of CV risk error-introducing. The indexation we proposed might help distinguish the effects of body weight gain from the ones resulting from the presence of certain cardiovascular diseases.